EDUKASI PENGENALAN KESEHATAN REPRODUKSI PADA ANAK DAN REMAJA DI SMP ISLAM AL-AZHAR 32 TAHUN 2023 - Nova. R; Mufidah. N; Vionisham. C.A (Yayasan Nusantara Hasana Berdikari, 2023)
The free association of teenagers in the millennial era often becomes a polemic. The millennial era is moving faster along with technological developments that have added value with easy access to all information and ins and outs about adult shows that cause teenagers to fall into promiscuity, such as free sex, cases of fights and alcoholics. Sex outside of marriage comes with negative risks to adolescents such as: psychological disorders, pregnancy out of wedlock, abortion, malnourished children, infant mortality at birth and even the death of young mothers. The things mentioned above can happen if teenagers are not given good education from an early age about the dangers of promiscuity. There are still many teenagers who do not understand about their reproductive health. It is necessary to carry out counseling to increase adolescent knowledge about reproductive health introduction education in children and adolescents. The method used in this activity is counseling through direct lectures by extension workers from the community service team; the media used are in the form of power points and leaflets; the counseling participants consisted of 99 young students of Al-Azhar Islamic Middle School 32. Prior to counseling, the distribution of pre-test links was carried out (filling in via Google form); and when the extension was finished, the post-test link was distributed (filling in the Google form). The answers from each counseling participant both during the pre-test and post-test were then analyzed using parametric statistics. Each pre-test score and post-test score were tested for normality to determine the distribution of the data. Then a paired sample T test was carried out to see the effect of reproductive health education on children and adolescents before and after counseling. The analysis of the data used a statistical software application. The results of this activity revealed that of the 99 students who attended educational counseling on reproduction in children and adolescents at Alazhar 32 Islamic Middle School were analyzed. There is an 82.73% increase in the average score of students' knowledge after counseling. The average score of students before counseling was 77.34%, p<0.05. The results of parametric statistics using the paired sample T test showed that counseling using interactive power point media and leaflets had an effect on changes in the average score of adolescent knowledge about reproductive health before and after counseling. The conclusion from this activity was that educational counseling on reproduction introduction to children and adolescents at Alazhar 32 Islamic Middle School. Knowledge before counseling was 77.34%; after counseling was 82.73%, p <0.05.